Electronic Banking Innovations and Selected Banks Performance in Nigeria - Orji, Anthony; Ogbuabor, Jonathan E; Okon, Asidok N; Anthony-Orji, Onyinye I (The Economics and Finance Letters, 2018)
In the past few years, Nigerian banks have embraced the global trend of digitalization in banking operations. Thus, after the consolidation and recapitalization exercises, many banks have strengthened and streamlined their facilities, tailored their services as well as automated their operations. In the heat of competition, banks are now adding to the stock of e-banking in order to maintain a competitive edge over their competitors. However, despite the rapid development in electronic banking innovations, it is not clear whether e-banking innovations have impacted positively and significantly on banks’ performance in Nigeria. The main objective of this paper therefore is to estimate the impact of e-banking innovations (ATM transactions, mobile banking transactions, and point of sales transactions) on the performance of six selected banks in Nigeria. The study adopts a SURE model in the quantitative analysis of six selected old and new generation banks. The results indicate that automated teller machine transactions, point of sale transactions, mobile banking transactions are major e-banking innovations that contribute to old and new banks’ performance in Nigeria. The study therefore concludes that the selected banks and other banks should intensify efforts to increase their asset base and continue to invest in e-banking innovations in order keep preforming well and also remain profitable. The study also calls for efficient management and utilization of funds to train and educate bank workers and general public regularly on how to deploy and use e-banking channels and other related technological innovations respectively.